Peptide receptors. - Quirion, Remi, 1955-; Bjorklund, Anders, 1945-; Hokfelt, Tomas (Handbook of chemical neuroanatomy, 2000)
During the last few years, the pace of research in the field of neuropeptide receptors has increased steadily: new neuropeptides were discovered, and the classification of receptor subtypes has been refined. It thus appeared essential to update the information. Peptide Receptors Part I summarizes current knowledge on ten distinct peptide families. This volume integrates photomontages and maps of quantitative receptor autoradiography, in situ hybridization histochemistry, and immunocytochemistry images. Application of these classical techniques and of new approaches such as transgenic and knock-out animals has revealed a distinct species and tissue specific variation in receptor subtypes expression and pharmacology in the mammalian central nervous system. The functional role of neuropeptides and their receptors in the CNS has been investigated thanks to the development of potent and selective receptor antagonists and agonists. The development of specific neuropeptide-related molecules will help to get a better understanding of receptor subtype physiology and neuronal distribution and may lead to innovative treatments in a variety of brain disorders.